QUOTA: The Quantile Option Architecture for Reinforcement Learning - Zhang, Shangtong; Yao, Hengshuai (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
In this paper, we propose the Quantile Option Architecture (QUOTA) for exploration based on recent advances in distributional reinforcement learning (RL). In QUOTA, decision making is based on quantiles of a value distribution, not only the mean. QUOTA provides a new dimension for exploration via making use of both optimism and pessimism of a value distribution. We demonstrate the performance advantage of QUOTA in both challenging video games and physical robot simulators.